Amphiphilic 2-Ethyl Hexyl Methacrylate-B-N,N?-Dimethylacrylamide Diblock Copolymer Monolayer Behaviour at the Air-Water Interface - Encina-Rojas, M (John Wiley and Sons Ltd, 2015)
Two samples of amphiphilic diblock-copolymers containing hydrophobic blocks of different length were studied as models for contribute to the understanding of surface characteristics of polymeric monolayers and thin films. The surface activities of two amphiphilic diblock copolymers containing 2-ethyl hexyl methacrylate-b-N,N′-dimethylacrylamide (EHMA-b-DMA) possessing hydrophobic segments of different chain lengths were studied. Toward this end, surface pressure-area (π-A) isotherms, static and dynamic elasticities and the ν exponent of the excluded volume of polymers forming monolayers at the air-water interface were measured. The degree of hydrophobicity of the diblock copolymers was estimated by determining their surface energy values from contact angle measurements. The morphology of the monolayer at different surface pressures was studied by Brewster angle microscopy. Both copolymers were observed to form stable and elastic monolayers, and their collapse was observed to occur at similar surface pressures. Langmuir-Blodgett films were successfully deposited onto mica and silicon wafers and analysed by atomic force microscopy. © 2014 Society of Chemical Industry.